2017
DOI: 10.1002/jcp.26222
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive transcriptome analysis of fluid shear stress altered gene expression in renal epithelial cells

Abstract: Renal epithelial cells are exposed to mechanical forces due to flow‐induced shear stress within the nephrons. Shear stress is altered in renal diseases caused by tubular dilation, obstruction, and hyperfiltration, which occur to compensate for lost nephrons. Fundamental in regulation of shear stress are primary cilia and other mechano‐sensors, and defects in cilia formation and function have profound effects on development and physiology of kidneys and other organs. We applied RNA sequencing to get a comprehen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 80 publications
1
33
0
Order By: Relevance
“…The cell culture was performed using a protocol described previously in our studies 12,13 . A Caco-2 cell line (HTB-37), derived from a human colorectal adenocarcinoma (ATCC, Manassas, VA, USA), were grown (at passage number [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] in DMEM supplemented with 1% penicillin/streptomycin, 1% MEM non-essential amino acid and 10% FBS, further indicated as DMEM + .…”
Section: Methodsmentioning
confidence: 99%
“…The cell culture was performed using a protocol described previously in our studies 12,13 . A Caco-2 cell line (HTB-37), derived from a human colorectal adenocarcinoma (ATCC, Manassas, VA, USA), were grown (at passage number [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] in DMEM supplemented with 1% penicillin/streptomycin, 1% MEM non-essential amino acid and 10% FBS, further indicated as DMEM + .…”
Section: Methodsmentioning
confidence: 99%
“…To our knowledge, no study has focused on the correlation between ADPKD and the ADM/IER3 genes. However, MYC/ADM/IER3 frequently appear in the lists of upregulated DEGs identified via transcriptomic analyses in various ADPKD-related studies [25,26,[49][50][51][52][53]. In addition, adrenomedullin, encoded by ADM, is a potent hypotensive peptide and has been associated with hypertension and chronic kidney disease (CKD) [54,55].…”
Section: Resultsmentioning
confidence: 99%
“…Identification of the differentially expressed gene (DEG) set (adjusted p-value ≤ 0.05 and |log 2 Fold Change| ≥ 0.26) was then performed with the DESeq2 (version 1.26.0) package [24]. In addition, a threshold counts per million (CPM) value was set to exclude hits with low expression levels (CPM < 2) [25,26]. The expression data were submitted to the Gene Expression Omnibus with the following accession number: GSE141355.…”
Section: Rna-seqmentioning
confidence: 99%
“…From a conceptual point of view, MPS models are valuable for drug transport-focused assays because they provide a system that allows correct polarization of cells with a clear basolateral to apical separation, expression of the corresponding native array of transporters, and formation of a highly tight epithelium that can selectively move molecules between compartments. Exposure to laminar flow sustains mechanosensitive responses that reshape the cellular transcriptome and upregulate expression of adhesion molecules (White and Frangos, 2007;Kunnen et al, 2018), and this stimulus has been shown to augment the expression of drug transporters in vitro (Nieskens and Wilmer, 2016).…”
Section: Drug Transporter Characterization In Mps Modelsmentioning
confidence: 99%